A prática interdisciplinar na política de assistência social: o caso das CRAS de Abaetetuba-PA - DALMASO, Karla (2010)
This Master Thesis in Social Work aims to make a reflection on interdisciplinary practice between assistants and psychologists working in the Centres of Reference for Social Welfare of the municipality of Abaetetuba. The city is located about 80 km from the capital of Pará State and has approximately 139,000 inhabitants, according to the last IBGE census. Since 2005 has been seeking to implement the National Policy of Social Welfare 2004. The New National Policy for Social Welfare, through its guidelines and seeks to consolidate the main objectives of decentralization of management. Establishing a new model socioassistenciais services organization, seeking to unify concepts and procedures throughout the country through the System of Social Assistance which, in turn, establishes standards for the performance of services, to quality care, and sets of assessment indicators and outcome. Interdisciplinarity can still be considered a concept in development, however this reality appears as a reciprocal relationship of mutuality that requires a different attitude to be taken regarding the problems of knowledge, that is to replace the fragmented conception of human unity. This attitude can not be prejudiced, but open where all knowledge becomes important, may be based on intersubjectivity and interaction between the knowledge, but can not be divorced from the context within which it occurs. The interdisciplinary performance practice at the Centre of Reference for Social Welfare, as well as projects in other programs and services of this policy is encouraged, but in reality the county investigated here showed that there are many obstacles and challenges to the exercise of that practice. Since non-compliance with regulations that govern the Social Assistance Policy to overcome the precarious conditions in working relationships, both with respect to the bond, as the physical and material spaces, through the need to implement management oriented qualification and human resources development included in the SUAS.